BIOPROSPEK MIKROALGA DI PESISIR MUARA PUTAT PULAU LOMBOK - Sri Puji Astuti; Baiq Farista; Arben Virgota (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Aquatic biodiversity in Muara Putat Estuary, Lombok Utara Regency, Lombok Island is the result of nutrient enrichment in the coastal. A complex combination of natural factors that support the growth of barriers in mangrove plants, agricultural and plantations, fish and aquatic invertebrates that regulate during the summer and rainy seasons. As a source of knowledge, biodiversity of aquatic microalgae is a major producer of nutrient chains in the estuary, habitat diversity will affect the source and regulation of aquatic nutrition. Studying microalgae is one of the important tools to determine the condition of an estuary and microalgae bioprospecting in the future. This study aims to determine the prospect of microalgae species found in Muara Putat waters during the summer and rainy season as well as to record the types of local microalgae found in these waters. Water samples are collected at 3 stations covering upstream, middle, and downstream estuary. Measures were carried out on the value of environmental supporting factors such as pH, water temperature, salinity, brightness, and currents. Obtained two local species that dominated the Bacillariophyceae and Chlorophyceae classes, with both of bioprospects that were sufficiently able to act as bio-indicators of aquatic saprobity, biochemical characteristics with various contents, could be as an agent of the Controlled Ecological Life Support System (CELSS), and produces certain metabolites based on changes in aquatic nutrient concentrations.